2008
DOI: 10.1038/jcbfm.2008.126
|View full text |Cite
|
Sign up to set email alerts
|

GABA Synapses Mediate Neuroprotection after Ischemic and εPKC Preconditioning in Rat Hippocampal Slice Cultures

Abstract: Delayed neuroprotection against ischemic challenges is conferred by both ischemic preconditioning (IPC) and preconditioning by activation of the e-isoform of protein kinase C (ePKC-PC). In vivo, ischemic preconditioning enhances GABA release and ameliorates glutamate release during lethal cerebral ischemia. We tested the hypothesis that IPC and ePKC-PC confer neuroprotection by GABA synapses in rat organotypic hippocampal slices. Ischemic preconditioning or ePKC-PC was induced with 15 mins oxygen-glucose depri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…33 The role for PKC in cerebral tolerance has been verified using various in vitro models in which PKC was activated after a preconditioning stimulus, such as application of ischemia or adenosine or NMDA, and was required for preconditioning-induced protection. 12,15,20,34 Similar to these studies in vitro, using an in vivo animal model PKC isoformspecific membrane translocation and protein expression in brain regions in intact mice with hypoxic preconditioning was investigated. Those results demonstrated that the development of cerebral hypoxic preconditioning was accompanied by an obvious increase in membrane translocation of PKC in the cortex and hippocampus, but no significant changes were noted in the membrane translocation of other PKC isoforms or in the whole protein expression of all 11 PKC isoforms, suggesting that activation of PKC might be involved in the development of cerebral hypoxic preconditioning of mice.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…33 The role for PKC in cerebral tolerance has been verified using various in vitro models in which PKC was activated after a preconditioning stimulus, such as application of ischemia or adenosine or NMDA, and was required for preconditioning-induced protection. 12,15,20,34 Similar to these studies in vitro, using an in vivo animal model PKC isoformspecific membrane translocation and protein expression in brain regions in intact mice with hypoxic preconditioning was investigated. Those results demonstrated that the development of cerebral hypoxic preconditioning was accompanied by an obvious increase in membrane translocation of PKC in the cortex and hippocampus, but no significant changes were noted in the membrane translocation of other PKC isoforms or in the whole protein expression of all 11 PKC isoforms, suggesting that activation of PKC might be involved in the development of cerebral hypoxic preconditioning of mice.…”
Section: Discussionmentioning
confidence: 90%
“…8 -11 Interestingly, among the different PKC isozymes, multiple studies have now demonstrated that epsilon PKC (PKC) was a key player in the induction of ischemic tolerance in various models of preconditioning. [12][13][14][15] Furthermore, a recent study reported that PKC confers acute tolerance to cerebral ischemic/reperfusion injury. 10 Based on these findings, the present study was undertaken to test the hypothesis that an activation of PKC was involved in EA pretreatment-induced neuroprotection via CB1 receptors in rat model of transient focal cerebral ischemia.…”
mentioning
confidence: 99%
“…Previous studies already showed that GABA A receptor agonists such as muscimol, barbiturates and volatile anesthetic agents were effective in neuroprotection in some models of cerebral ischemia [19,29,35]. It is possible that the characteristics of GABA A receptors in modulating rCBF and BBB in cerebral ischemia could have contributed to the neuroprotection reported by other animal studies.…”
Section: Discussionmentioning
confidence: 90%
“…In vivo, however, they could act differently because of interactions with neurons, neurotransmitters, and other chemicals present. Most of the GABA agonists have been known to decrease cerebral metabolism and rCBF, and provide some type of neuroprotection in in vivo and in vitro studies [6,[27][28][29]. Neurotransmitters may also alter cerebral capillary diameter by affecting pericytes in the microvasculature [30].…”
Section: Discussionmentioning
confidence: 98%
“…εPKC preconditioning increases the average amplitude of GABA-related inhibitory post-synaptic events [159], maintains ion homeostasis during ischemia by inhibiting Na + /K + -ATPase and voltage gated Na + channels [160], improves cerebral blood flow [161], and phosphorylates the mitochondrial K + ATP channel [162]. The plethora of responses that are produced from εPKC activation indicates the necessity for a preconditioning agent to have numerous targets for neuroprotection or IPC mimetic.…”
Section: Synaptic Neuroprotectionmentioning
confidence: 99%